Ultrasound and clinical-morphological evaluation of fetal-placental complex of pregnant women with intrauterine infection - S M Voevodin; T V Shemanaeva; A I Shchegolev (IP Berlin A.V., 2015)
Analysis of ultrasound and clinical and morphological data of 52 cases complicated by placental insufficiency and the presence of intrauterine infection have performed. In all cases, pathomorphological verification of the placenta had carried out. Ultrasound markers-predictors of early complications of placental insufficiency and intrauterine infection had identified.